First case report of a novel KIF13A-ALK fusion in a lung adenocarcinoma patient and response to alectinib with a 4-year follow-up - Mo, Zheng; Cai, Cunliang; Yao, Jingjing; Zhao, Jingquan; Zhang, Mingqiang; Liu, Hao; Mu, Xiangdong (Frontiers in Genetics, 2023)
The prevalence of Anaplastic Lymphoma Kinase gene (ALK) fusion is about 5% among patients with lung adenocarcinoma, underscoring the importance of pinpointing distinct fusion variants for optimizing treatment approaches. This is the first reported case of a 74-year-old female with stage IV lung adenocarcinoma, featuring a novel Kinesin Family Member 13A (KIF13A)-ALK fusion, identified via next-generation sequencing (NGS) and confirmed with fluorescence in situ hybridization (FISH). Initially undergoing chemotherapy and then crizotinib, she achieved a partial response (PR) before progressing with multiple bone metastases. However, subsequent treatment with alectinib as a third-line option yielded positive results. A stable disease state persisted for an impressive 31 months of progression-free survival (PFS), accompanied by minimal toxicity symptoms. Up until now, a remarkable near 4-year span of overall survival (OS) has been consistently observed and monitored. This report of a KIF13A-ALK fusion case benefit significantly from alectinib with extensive follow-up.The case diversifies the array of ALK fusion partners and holds clinical relevance in refining therapeutic choices for KIF13A-ALK fusion-associated lung cancer.